Awareness and willingness to utilize HIV pre-exposure prophylaxis and associated factors among men who have sex with men in Maanshan, China - Quan Fang; Gan Tang; Ziwei Wang; Qian Guo; Qisheng Guo; Yinguang Fan; Qirong Qin (PLoS ONE, 2025)
Objective Men who have sex with men (MSM) are disproportionately affected by HIV and represent the primary target population for pre-exposure prophylaxis (PrEP) use. However, PrEP adoption in China remains limited, partly due to its late regulatory approval. This study aims to investigate the awareness and willingness of PrEP use and associated factors among MSM in Maanshan city, so as to promote the popularization of PrEP. Methods This cross-sectional study was conducted in Maanshan City, China, between June 2016 and December 2019. Participants completed the questionnaire through respondent-driven sampling (RDS). The questionnaire information was organized and analyzed using SPSS 23.0 software. Both univariate and multivariate logistic regression models were employed to investigate the determinants of PrEP willingness and awareness among HIV-negative MSM. Results A total of 879 participants were enrolled, with 837 providing analyzable data. The majority (62.25%) were aged <30 years old, with 97.49% self-identified as homosexual. Among participants, 50.18% reported regular male sexual partners. Regarding sexual behaviors, 71.80% of MSM engaged in casual sex and 36.56% unprotected anal sex (UAI) within the last six months. HIV awareness was reported by 92.83% of respondents, while PrEP awareness was substantially lower (22.70%). Willingness to use PrEP was high (89.49%), with 16.49% preferring to take PrEP daily and 84.59% preferring to take PrEP on demand. Multivariate logistic regression revealed that vocational school (vs. high school or below), recent casual sex engagement, PrEP awareness, and recent UAI history were significant predictors of PrEP willingness. Higher education (university or above vs. high school or below), versatile sexual role (vs. op/insertive ones), recent casual sex and prior HIV testing were positively associated with PrEP awareness. Conclusions Maanshan’s MSM population demonstrated high PrEP acceptance but limited awareness. The findings suggest that expanding access to HIV testing could enhance PrEP awareness. Simultaneously, PrEP dissemination combined with targeted HIV prevention may effectively reduce HIV transmission in the MSM population.